Development of A Web-Based Dominance, Influence, Steadiness, Compliance, (DISC) Test Platform With A Career Recommendation System For Optimizing Career Decision Making in Generation Z - Novitasari, Chandani; Sulistyo Sarjowo, Mochammad Imam; -, Minarto (RISTEC : Research in Information Systems and Technology, 2025)
Generation Z is a cohort that has grown up in the digital era, characterized by their adaptability to technology and preference for flexible careers aligned with their personality. However, many individuals from this generation often experience confusion in determining their career paths due to a lack of self-awareness and job compatibility. This study aims to develop a web-based DISC personality test platform equipped with a career recommendation system to assist Generation Z in making accurate career decisions. The research method used is Research and Development (R&D) with a software development approach using the waterfall model. The system enables users to take the DISC test, receive personality result, and obtain career recommendation based on the trait and factor psychological approach. Testing result indicate that the system function well, is user-friendly, and provides accurate and relevant outcomes tailored to user needs. This platform is expected to serve as an effective tool in supporting career decision-making for generation Z.